Prevention of mother-to-child transmission of HIV Option B+ cascade in rural Tanzania: The One Stop Clinic model. - Anna Gamell; Lameck Bonaventure Luwanda; Aneth Vedastus Kalinjuma; Leila Samson; Alex John Ntamatungiro; Maja Weisser; Winfrid Gingo; Marcel Tanner; Christoph Hatz; Emilio Letang; Manuel Battegay; KIULARCO Study Group (PLoS ONE, 2017)
Strategies to improve the uptake of Prevention of Mother-To-Child Transmission of HIV (PMTCT) are needed. We integrated HIV and maternal, newborn and child health services in a One Stop Clinic to improve the PMTCT cascade in a rural Tanzanian setting.The One Stop Clinic of Ifakara offers integral care to HIV-infected pregnant women and their families at one single place and time. All pregnant women and HIV-exposed infants attended during the first year of Option B+ implementation (04/2014-03/2015) were included. PMTCT was assessed at the antenatal clinic (ANC), HIV care and labour ward, and compared with the pre-B+ period. We also characterised HIV-infected pregnant women and evaluated the MTCT rate.1,579 women attended the ANC. Seven (0.4%) were known to be HIV-infected. Of the remainder, 98.5% (1,548/1,572) were offered an HIV test, 94% (1,456/1,548) accepted and 38 (2.6%) tested HIV-positive. 51 were re-screened for HIV during late pregnancy and one had seroconverted. The HIV prevalence at the ANC was 3.1% (46/1,463). Of the 39 newly diagnosed women, 35 (90%) were linked to care. HIV test was offered to >98% of ANC clients during both the pre- and post-B+ periods. During the post-B+ period, test acceptance (94% versus 90.5%, p<0.0001) and linkage to care (90% versus 26%, p<0.0001) increased. Ten additional women diagnosed outside the ANC were linked to care. 82% (37/45) of these newly-enrolled women started antiretroviral treatment (ART). After a median time of 17 months, 27% (12/45) were lost to follow-up. 79 women under HIV care became pregnant and all received ART. After a median follow-up time of 19 months, 6% (5/79) had been lost. 5,727 women delivered at the hospital, 20% (1,155/5,727) had unknown HIV serostatus. Of these, 30% (345/1,155) were tested for HIV, and 18/345 (5.2%) were HIV-positive. Compared to the pre-B+ period more women were tested during labour (30% versus 2.4%, p<0.0001). During the study, the MTCT rate was 2.2%.The implementation of Option B+ through an integrated service delivery model resulted in universal HIV testing in the ANC, high rates of linkage to care, and MTCT below the elimination threshold. However, HIV testing in late pregnancy and labour, and retention during early ART need to be improved.